Understanding solid solution strengthening at elevated temperatures in a creep-resistant Mg–Gd–Ca alloy. (December 2019) - Mo, Ning; McCarroll, Ingrid; Tan, Qiyang; Ceguerra, Anna; Liu, Ying; Cairney, Julie; Dieringa, Hajo; Huang, Yuanding; Jiang, Bin; Pan, Fusheng; Bermingham, Michael; Zhang, Ming-Xing
Abstract: The present work studies the strengthening mechanisms of a creep-resistant Mg-0.5Gd-1.2Ca (at.%) alloy at both room and elevated temperatures. Although peak-ageing (T6) at 180 °C for 32 h led to a significant increase in room temperature strength due to the precipitation strengthening by three types of precipitates (Mg2 Ca, Mg5 Gd on prismatic planes and a new type of Mg–Gd–Ca intermetallic compound on the basal plane), the as-solid solution treated (T4) alloy exhibited better resistance to temperature softening during compression and to stress relaxation at 180 °C and better creep resistance at 210 °C/100 MPa. The Gd–Ca co-clusters with short-range order in the Mg solid solution, which was verified, at the first time, by atom probe tomography (APT) analysis and atomic-resolution high angle annular dark field-scanning transmission electron microscopy (HAADF-STEM), were responsible for the solid solution hardening, offering a more effective strengthening effect through local order-strengthening. Such solid solution strengthening increased the thermal stability of the alloy structure at elevated temperatures, at least at early stage of the creep. Subsequently, dynamic precipitation started contributing to the creep resistance due to the formation of higher density of precipitates. However, in the T6 alloy, creep testing at elevated temperatures, particularly at 210 °C that was higher than the ageing temperature, led to coarsening of the precipitates, which acted as over ageing. As a result of such over ageing, the resistance of the T6 alloy to heat-induced softening was weakened, leading to lower creep resistance than the T4 alloy. Graphical abstract: Image, graphical abstract